2020
DOI: 10.1103/physrevresearch.2.023099
|View full text |Cite
|
Sign up to set email alerts
|

Realizing split-pulse x-ray photon correlation spectroscopy to measure ultrafast dynamics in complex matter

Abstract: Split-pulse x-ray photon correlation spectroscopy has been proposed as one of the unique capabilities made possible with the x-ray free electron lasers. It enables characterization of atomic scale structural dynamics that dictates the macroscopic properties of various disordered material systems. Central to the experimental concept are x-ray optics that are capable of splitting individual coherent femtosecond x-ray pulse into two distinct pulses, introduce an adjustable time delay between them, and then recomb… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 28 publications
0
13
0
Order By: Relevance
“…Depending on the magnitude of the overlap and angular misalignment, a proper binning of the detector along the direction of angular misalignment can partially recover the contrast. Recently, Sun et al (2020) proposed another approach to compensate for the shift of the speckle pattern by evaluating the autocorrelation function. In principle, both techniques yield similar results in partially recovering the original contrast, and should act as complementary tools to verify the results in a double-probe XSVS experiment.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Depending on the magnitude of the overlap and angular misalignment, a proper binning of the detector along the direction of angular misalignment can partially recover the contrast. Recently, Sun et al (2020) proposed another approach to compensate for the shift of the speckle pattern by evaluating the autocorrelation function. In principle, both techniques yield similar results in partially recovering the original contrast, and should act as complementary tools to verify the results in a double-probe XSVS experiment.…”
Section: Resultsmentioning
confidence: 99%
“…The experimental setup in this case uses optics in a split-and-delay line to separate a coherent pulse into two identical probes, delaying one of the probes in time, and recombining them into two collinear signals (Yabashi et al, 2017). In practice, this is extremely difficult to achieve consistently (Sun et al, 2020), and there will often be an angular misalignment between the two pulses and a nonperfect overlap on the sample as illustrated in Fig. 1(b).…”
Section: X-ray Speckle Visibility Spectroscopymentioning
confidence: 99%
See 1 more Smart Citation
“…This contrast reduction can be reasonably explained by the degree of decoherence between the sub-pulses. The angular mismatch parallel to the detector plane between the sub-pulses 50 , 0.15 mrad, creates the positional difference between two speckles ~ 0.15 mm on the detector plane, thereby reducing the contrast from 0.23 to ~0.15 ~ β ( Q , Δ t = 0). Note that the angular mismatch perpendicular to the detector plane can be ignored.…”
Section: Discussionmentioning
confidence: 99%
“…At present, two modes of XPCS studies have been discussed and demonstrated at XFELs: (1) the sequential mode, where one XPCS speckle pattern is collected per X-ray pulse [19,20], similar to synchrotron-based XPCS experiments; (2) the split-pulse mode [16,[21][22][23][24][25], where one ultrafast X-ray pulse is split into two, and subsequently recombined with a relative delay from a few picoseconds up to nanoseconds. In the latter mode, each image collected from the X-ray detector is the sum of speckle intensities from two pulses.…”
Section: Introductionmentioning
confidence: 99%